The Effect of Rational Motivations, Emotional Motivations, Promotions, and Brand Images on the Purchase Decision of Yamaha Motorcycles at Alfa Scorpii Rantauprapat - Ade Indah Sari Harahap; Ade Parlaungan Nasution; Elida Florentina Sinaga Simanjorang (Budapest International Research and Critics University, 2021)
This study aims to determine the effect of rational motives, emotional motives, promotions, and brand image on motorcycle purchasing decisions on Yamaha consumers at Alfa Scorpii Rantauprapat. Purposive sampling is a sampling technique in this study. Research data obtained by distributing research questionnaires to 89 respondents. The data analysis technique used is Multiple Linear Regression Analysis, F Test, t Test, and Coefficient of Determination, using the help of the IBM SPSS Statistics 16 application. The results show that (1) rational motives and emotional motives partially influence purchasing decisions ( 2) promotion, and brand image partially have no effect on purchasing decisions (3) rational motives, emotional motives, promotions, and brand image simultaneously affect purchasing decisions (4) the results of the Multiple Linear Regression equation are Y = 2.204 + 0.326X + 0.358X + 0.045X + 0.132X and (4). the value of the coefficient of determination is 0.313.